A Universal Chemotactic Targeted Delivery Strategy for Inflammatory Diseases. Issue 47 (17th October 2022) - Li, Ting; Liu, Zhiyong; Hu, Jinglei; Chen, Lin; Chen, Tiantian; Tang, Qianqian; Yu, Bixia; Zhao, Bo; Mao, Chun; Wan, Mimi
Abstract: Above 50% of deaths can be attributed to chronic inflammatory diseases; thus, the construction of drug delivery systems based on effective interaction of inflammatory factors with chemotactic nanoparticles is meaningful. Herein, a zwitterion‐based artificial chemotactic nanomotor is proposed for universal precise targeting strategy in vivo, where the high level of reactive oxygen species (ROS) and inducible nitric oxide synthase (iNOS) in inflammatory sites are used as a chemoattractant. Multidimensional static models, dynamic models, and in vivo models are established to evaluate chemotactic performance. The results show that the upregulated ROS and iNOS can induce the chemotaxis of nanomotors to diseased tissues in inflammation‐related disease models. Further, mesoscale hydrodynamics simulations are performed to explain the chemotactic behavior of the nanomotors. Such a chemotactic delivery strategy is expected to improve delivery efficiency and may be applicable to a variety of inflammatory diseases. Abstract : An artificial chemotaxis system that shows positive chemotaxis to high concentration of inducible nitric oxide synthase and reactive oxygen species is proposed, which can precisely target inflammatory sites in vivo. Such a universal chemotactic delivery strategy aimed at the inflammatory microenvironment, can possibly avoid the problem of individual differences in the targeting strategies based on ligand‐receptor specific binding.